(untitled) (Fiep Bulletin - online, 2012)
The present study analyzed the hypothesis of the independent components of speed and accuracy to control fast and accurate movements. Twelve college students (right-handed) with mean age of 23 years old (SD=2,67) participated in the study. The task was performed moving a computer cursor controlled by a stylus and a digital table aiming spatial targets. It was manipulated the distance between targets, targets widths, and the direction to be tracked by the cursor. It was verified lower time movement in the condition in which there was no direction change, in comparison to the other conditions (P<0,05). Therefore, it was not provided evidence to support the hypothesis of the independence between speed-accuracy. Such results were explained by the great constraint provided in the conditions with change of direction and by the fact that linear movements performed in the software were the result of joint angular actions from the upper limbs.